Performance Analysis On Segmented Interior Permanent Magnet Synchronous Motor (IPMSM) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Permanent magnet synchronous motor (PMSM) is an ac motor that uses a magnet inserted into the rotor or mounted on the surface of the motor rotor. In this study, the conventional and segmented interior permanent magnet synchronous motor (IPMSM) will be constructed and analyzed for the best motor types. In the segmented IPMSM, the magnet of each pole is segmented, and between each segment, there exists a rotor iron bridge. Moreover, for the segmented IPMSM, there are three different designs of the width of the iron bridge, which is 2mm, 1mm and 0.5mm. All the design will be analyzed by using JMAG Designer software. Furthermore, no-load analysis is performed to evaluate cogging torque, flux linkage, flux distribution and back-EMF of the motor model. After that, load analysis will be conduct, which measures the torque-speed characteristics, output power, flux weakening and constant power speed range (CPSR) of each type of motor. In this project, a wide CPSR is achievable in segmented IPMSM due to its inherent flux-weakening capability. So, the maximum speed of the motor is higher in segmented than a conventional motor.